2021
DOI: 10.1002/mma.7360
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of fractional‐order COVID‐19 epidemic model with quarantine and social distancing

Abstract: Different countries of the world are facing a serious pandemic of corona virus disease (COVID‐19). One of the most typical treatments for COVID‐19 is social distancing, which includes lockdown; it will help to decrease the number of contacts for undiagnosed individuals. The main aim of this article is to construct and evaluate a fractional‐order COVID‐19 epidemic model with quarantine and social distancing. Laplace homotopy analysis method is used for a system of fractional differential equation (FDEs) with Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 39 publications
0
12
0
2
Order By: Relevance
“…For source data, SEIR is an excellent model that allows the COVID-19 outbreak in all nations with government policies and other endemic models [22] , [23] , [24] , [25] . A. Atanagana, Farman et al, [26] , [27] , [28] Numerical modelling and asymptomatic carrier transmission are used to investigate a mathematical model of a new Corona-virus (2019-nCoV). We adopted this approach for the calculations [29] , since the numerical data is in all nations.…”
Section: Introductionmentioning
confidence: 99%
“…For source data, SEIR is an excellent model that allows the COVID-19 outbreak in all nations with government policies and other endemic models [22] , [23] , [24] , [25] . A. Atanagana, Farman et al, [26] , [27] , [28] Numerical modelling and asymptomatic carrier transmission are used to investigate a mathematical model of a new Corona-virus (2019-nCoV). We adopted this approach for the calculations [29] , since the numerical data is in all nations.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect spread can be through mediums that are commonly touched by humans, such as table, office tools, and so on. The patients with strong immune systems cause them to have no symptoms (they are called asymptomatic infected) [16], [27], [36]. Therefore, COVID-19 is of global concern because patients are difficult to detect and spread quickly.…”
Section: Introduction Coronavirus Disease 2019 (Covid-19mentioning
confidence: 99%
“…COVID-19 patients who have high immunity may become an asymptomatic infected. This individual group differs from exposed individuals who are developing the virus but are not infectious [16], [27]. Megasari et al [29] have reported asymptomatic infections in East Java, Indonesia have spread which is characterized by a high prevalence of infection.…”
Section: Introduction Coronavirus Disease 2019 (Covid-19mentioning
confidence: 99%
“…Non-integer order calculus, known as fractional calculus (FC), generalizes integral and differential calculus. Briefly, fractional order (FO) operators can be representative of memory functions, making the dynamics of variables more realistic [18] , [19] , [20] . Recent studies on CoViD-19 have incorporated FC [21] , [22] , [23] , [24] .…”
Section: Introductionmentioning
confidence: 99%